2016
DOI: 10.1007/s12194-015-0344-z
|View full text |Cite
|
Sign up to set email alerts
|

Liver acquisition with volume acceleration flex on 70-cm wide-bore and 60-cm conventional-bore 3.0-T MRI

Abstract: This study aimed to compare the uniformity of fat suppression and image quality between liver acquisition with volume acceleration flex (LAVA-Flex) and LAVA on 60-cm conventional-bore and 70-cm wide-bore 3.0-T magnetic resonance imaging (MRI). The uniformity of fat suppression by LAVA-Flex and LAVA was assessed as the efficiency of suppression of superficial fat at the levels of the liver dome, porta, and renal hilum. Percentage standard deviation (%SD) was calculated using the following equation: %SD (%) = 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…This could be a concern for larger patients. A wide‐bore (70 cm) MRI scanner can be used for DCE‐MRI if necessary, as it has demonstrated comparable performance to a closed‐bore (60 cm) MR scanner for abdominal imaging . However, B1 field inhomogeneity may be increased in wide‐bore MRI scanners, so a reliable method of B1 mapping will need to be used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be a concern for larger patients. A wide‐bore (70 cm) MRI scanner can be used for DCE‐MRI if necessary, as it has demonstrated comparable performance to a closed‐bore (60 cm) MR scanner for abdominal imaging . However, B1 field inhomogeneity may be increased in wide‐bore MRI scanners, so a reliable method of B1 mapping will need to be used.…”
Section: Discussionmentioning
confidence: 99%
“…A wide-bore (70 cm) MRI scanner can be used for DCE-MRI if necessary, as it has demonstrated comparable performance to a closed-bore (60 cm) MR scanner for abdominal imaging. 40 However, B1 field inhomogeneity may be increased in wide-bore MRI scanners, so a reliable method of B1 mapping will need to be used. Eventually, the phantom package could be inserted within the MRI bed, but it would have to be included within the field of view and the surface coil.…”
Section: Discussionmentioning
confidence: 99%
“…To solve this problem, MRI manufacturers use various RF subsystems, including the total image matrix from Siemens, geometry-embracing method from GE, and dStream from Philips, to improve the magnet homogeneity (Sobol, 2012 ). The results of clinical practice have showed that a 70-cm wide-bore magnet system has realized the perfect combination of the high-quality imaging with the patient comfort (Kim et al, 2015 ; Tarnoki et al, 2015 ; Saito et al, 2016 ). In this study the high resolution spectra of metabolites included glutamate are acquired reliably at a 70-cm wide-bore magnet system.…”
Section: Discussionmentioning
confidence: 99%
“…T2w FS images are sensitive to water tissue content, and CE T1w can show enhancing regions within the tumor and distinguish necrosis and solid tumor . Compared with conventional fat suppression T1‐weighed images, LAVA‐Flex can offer superior image quality, less motion artifact, and more homogenous fat suppression, as has been shown in skeletal tumors …”
mentioning
confidence: 99%
“…5 Compared with conventional fat suppression T1-weighed images, LAVA-Flex can offer superior image quality, less motion artifact, and more homogenous fat suppression, as has been shown in skeletal tumors. [6][7][8] In clinical practice, however, SMT, SC, and SGCT share many common imaging characteristics.1 Although most patients are diagnosed by biopsy. Biopsies are invasive, and the result can vary largely depending on which part of the tumor is sampled due to tumor heterogeneity.…”
mentioning
confidence: 99%